Floristic Composition, Diversity and Carbon Stock Along Altitudinal Gradient in Hasantar Community Forest, in Nagarjun Municipality, Kathmandu District - Pradhan, Pranil; Sapkota, Divas; Banjara, Sudip; Karki , Sweta (Journal of Environment Sciences, 2023)
This study has attempted to estimate above and below ground biomass along altitudinal gradient and examined the relation between carbon stock and diversity indices. The study area was categorized into three sections based on the elevation interval of 200m ranging from 1300m to 1900m. Vegetation sampling was performed in 33 circular plots, each of 500m2 and was selected based on systematic random sampling. Phyto-sociological parameters and above and below ground biomass and total carbon stock were calculated for each section of the study area. Carbon stock showed negative and insignificant relation with species evenness (r=-0.24, P= 0.17) and positive but insignificant relation with species richness (r=0.17, p=0.34) and Simpson’s index of dominance (r=0.18, P=0.31). However, humped shaped and statistically insignificant (P=0.93) relationship was observed between Shannon diversity index and carbon stock. This research results provide baseline information for the management of Hasantar community forest.